Physics of food structure breakdown and bolus formation during oral processing of hard and soft solids. (June 2015) - Witt, Torsten; Stokes, Jason R
Graphical abstract: Highlights: Food design paradigms require solid food oral processing knowledge. Food structure and oral physiology affect fracture mechanics and particle size. Saliva and fluid release affect particle interactions, hydration and rheology. Emerging links between physics and temporal textural percepts. Mechanistic insight challenged by inter-individual differences in oral physiology. Abstract : Recent studies on the oral processing of hard and soft foods are presented with consideration for the underlying physics involved during the transformation of food to a semifluid bolus for swallowing. Significant insights are being realised about the temporal aspects of the dominant processes of comminution, agglomeration, hydration and dilution, and connections to the dominant textural properties are emerging. The field is still challenged by inter-individual differences in oral physiology, but in vitro approaches to characterise the evolution of the food bolus have the potential to provide structure–property–oral processing relationships. Integrated approaches and development of techniques to measure the in-use physics of oral processing are critical for advanced food structure design.